Arahan Penutupan Lahan Daerah Aliran Sungai Batu-batu sebagai Upaya Mitigasi Pendangkalan Danau Tempe - Chaeria Anila; Marleny Dara; Muhammad Dahri Syahbani Rusman; Sri Batara Nurfajri Arisaputri (Prodi PWK Universitas Tadulako, 2026)
The Lake Tempe ecosystem is one of Indonesia’s national priority lakes that requires restoration due to severe sedimentation. The lake plays an important role in supporting regional economic resilience, social sustainability, and community livelihoods. The natural shallowing of the lake is caused by sediment transported by rivers flowing into the lake, including the Batu-Batu River. Previous oceanographic and limnological studies identified the highest accumulation of Total Suspended Solids (TSS) at the Batu-Batu River estuary. This study aims to analyze sediment conditions and formulate appropriate land-use directions as a sedimentation mitigation strategy in the Batu-Batu Watershed. Sediment accumulation was simulated using the Soil and Water Assessment Tool (SWAT) hydrological model. Land-use recommendations were developed by considering areas with heavy and very heavy sedimentation classes, land capability classes, 2020 land cover conditions, and the 2032 Spatial Pattern Plan. The simulation results show that sediment production in 2020 reached 1,233,509.04 tons/year, indicating a high sedimentation rate. Under the 2032 spatial planning scenario, sediment yield is projected to increase by 30.10% compared to existing conditions. However, the proposed land-use directions could reduce sediment yield by 66.17%. These findings indicate that the proposed land-use strategy can be considered in future regional spatial planning and watershed management policies.